Development and validation of a questionnaire to evaluate the impact of COVID-19 on lifestyle-related behaviours: eating habits, activity and sleep behaviour. Issue 6 (16th April 2021) - Chopra, Sakshi; Ranjan, Piyush; Malhotra, Anita; Sahu, Anamika; Dwivedi, SN; Baitha, Upendra; Goel, Aastha; Kumar, Arvind
Abstract: Objective: This study was conducted to develop and validate a questionnaire to assess the impact of COVID-19 pandemic on lifestyle-related behaviour related to eating, activity and sleep pattern. Design: Indexed study used a mixed method design. Phase I employed qualitative methods for development of questionnaire including literature review, focus group discussion, expert evaluation and pre-testing. Phase II used quantitative methods for establishing construct validity of the questionnaire via parallel factor analysis. Participants: Phase 1 involved participation of experts from different fields (Departments of Medicine, Nutrition and Clinical Psychology) and general adult population. For phase II, data were collected from 124 adult respondents (female = 57·26 %); mean age (36 ± 14·8 years) residing in an urban setting. Results: The questionnaire consisted of three sections: (A) socio-demographic and anthropometric parameters, (B) twenty-four items each for investigating the changes in eating, activity and sleep behaviour before v . during COVID-19, (C) six items assessing COVID-19 specific reasons for lifestyle change. The Cronbach's α value of the questionnaire is 0·83 suggesting its good internal consistency. Conclusions: This appears to be a valid tool to assess the impact of COVID-19 on lifestyle-related behaviours with potential utility for public health researchers to identify these changes at community level and develop strategies to reinforce corrective behaviours.